30-Year Outcomes of Dental Implants Supporting Mandibular Fixed Dental Prostheses: A Retrospective Review of 4 Cases. Issue 5 (October 2015) - Turkyilmaz, Ilser; Tözüm, Tolga F.
Abstract : Purpose: The aim of this study was to present the 30-year outcomes of 28 implants supporting mandibular screw-retained fixed dental prostheses (FDPs). Materials and Methods: Dental charts of the 4 patients were carefully reviewed, and it was noticed that they received 28 implants and 5 screw-retained FDPs in 1983 and 1984. The chief concerns raised by these patients were poor retention of their complete dentures and decreased masticatory function at the time of treatment planning. Each dental care they received was recorded in the last 30 years. Implant survival, radiographic, and prosthodontic examinations were performed. Results: No implants were lost after 30 years, giving the implant a survival rate of 100%. The average marginal bone level was 2.6 ± 0.5 mm at the last recall appointment. Of the 5 FDPs delivered, 1 needed replacement, indicating a prosthesis survival rate of 80%. The patients needed 21 repairs such as replacement of denture teeth/gold screws and hard relining, and 19 adjustments such as occlusal adjustments and acrylic resin contouring, over 30 years. Conclusion: This clinical report shows that machined-surface dental implants can successfully support screw-retained fixed dental prostheses for over 30 years, making dental implants an important dental treatment alternative compared to the traditional prosthetic treatment methods.